Long-term clinical results and scanning electron microscopic analysis of the aspheric, hydrophobic, acrylic intraocular lens CT LUCIA 611P(Y) - Borkenstein AF (Dove Medical Press, 2018)
Andreas F Borkenstein, Eva-Maria Borkenstein Borkenstein & Borkenstein, Privatklinik der Kreuzschwestern, Graz, Austria Purpose: The aim of this study was to evaluate the clinical outcomes of a novel designed hydrophobic, acrylic, monofocal, fully preloaded intraocular lens (IOL; CT LUCIA 611P) 1 year after implantation. Scanning electron microscopic analysis regarding the optic–haptic junction and sharp edges of the IOL was performed. Patients and methods: This is a noninterventional, observational prospective study of cataract patients who underwent implantation of the CT LUCIA 611P. Ninety-six eyes of 54 subjects were enrolled. Follow-up included visual acuity assessment, slit lamp examination with special focus on appearance of glistenings and evaluation of posterior capsule opacification (PCO). Scanning electron microscopic analysis of the new designed optic–haptic junction and edges of the IOL was performed. Results: Best-corrected distance visual acuity increased from mean 0.48 logMAR (range 0.86–0.34) preoperatively to mean 0.02 logMAR (range 0.14 to -0.10) 1 year after surgery. Thirty-eight of 42 subjects’ eyes (90.5%), which underwent bilateral surgery with implantation of the IOL, never required glasses for distance again, while 4 (9.5%) required glasses only in rare cases (eg, driving at night). The spherical equivalent was within ±0.50 D in 88 of 96 subjects (91.7%) and within ±0.75 D in 96.9% of cases. Target refraction ±1.00 D was achieved in 100% of subject eyes. No glistenings were reported in any case. From the surgeons’ perspective, the wider, thicker optic–haptic transition of the IOL resulted in significantly increased stiffness, which enabled improved centering of the IOL and enhanced rotational stability and refractive predictability and stability and PCO prevention. Conclusion: The results of this long-term observational study demonstrate the safety and efficacy of the IOL. Because of the completely new designed thicker and stiffer optic–haptic junction regarding improved characteristics of the IOL (stability in the capsular bag), some special attention has to be addressed to the slightly different behavior of the lens during implantation and unfolding process. Keywords: intraocular lens, IOL, CT LUCIA 611P(Y), cataract surgery, quality of vision, aspheric design, glistenings, square edge, Achilles Heel of the IOL